The optimal exercise modality and intensity for hemodialysis patients incorporating Bayesian network meta-analysis and systematic review - Song, Yangyang; Chen, Lei; Wang, Meng; He, Quan; Xue, Jinhong; Jiang, Hongli (Frontiers in Physiology, 2022)
Background: Physical inactivity is highly prevalent in patients with hemodialysis, and a large body of evidence reported the positive effect of different exercise modalities on their health outcomes. However, the effective dosage of exercise for hemodialysis patients still requires verification. Objective: To determine the most effective exercise intensity and modality for improvements in physical function, blood pressure control, dialysis adequacy, and health-related quality of life for hemodialysis patients. Design: Systematic review with network meta-analysis of randomized trials. Data sources: Five electronic databases (Pubmed, Embase, Web of Science, Cochrane CENTRAL, and Scopus) were searched for randomized controlled trials. Data extraction and quality appraisal were conducted by two authors independently. Data were analyzed by the R (verson.3.6.2) and the Stata (version.15.0). Result: We included 1893 patients involving 4 exercise modalities and 6 exercise intensities. Combined training (aerobic exercise plus resistance exercise) has been the top-ranking exercise modality for improving the 6-minute walk test (6MWT) (surface under the cumulative ranking curve analysis (SUCRA) score, 90.63), systolic blood pressure control (SURCA score, 77.35) and diastolic pressure control (SURCA score, 90.56). Moreover, the top-ranking exercise intensity was moderate-vigorous intensity for 6MWT (SURCA score, 82.36), systolic blood pressure (SURCA score, 77.43), and diastolic blood pressure (SURCA score, 83.75). Regarding dialysis adequacy and health-related quality of life, we found no exercise modality or intensity superior to the placebo. Conclusions: This network meta-analysis indicated that combined training and moderate-vigorous intensity might be the most effective interventions to improve 6MWT and blood pressure control. This finding helps to further guide clinical exercise prescriptions for hemodialysis patients.